1911
DOI: 10.1002/cber.19110440309
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bildung von Isochinolin‐derivaten durch Einwirkung von Methylal auf Phenyl‐äthylamin, Phenyl‐alanin und Tyrosin

Abstract: Nehmen wir nun aber diesen Standpunkt an, so erwiichst von selbat die Frage, ob in dem von C o t t o n entdeckten Typus der anomalen Rotationsdispersion nicht etwa ein Grundtypus vorliegt, und ob man nicht die beiden anderen Typen als s e k u n d a r e UnregelmaBigkeiten in der allgemeinen Dispersionskurre zu betrachten hat.St. P e t e r s b u r g , Eude hlai 1911. Die zwei bis jetzt zur Synthese von Opiumalkaloiden benutzten Methoden von B i s c h l e r und N a p i e r a l s k i und von P i c t e t und G a m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
218
0
11

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 676 publications
(232 citation statements)
references
References 1 publication
3
218
0
11
Order By: Relevance
“…Its formation, therefore, seems to be due to the degradation of L-dopa or DL-serine to pyruvate by tyrosine phenol lyase in the cells and to the additional nonenzymatic reaction of pyruvate to L-dopa, known as the Pictet-Spengler reaction. 13 ) To isolate and identify X-I and X-2, 5 liters of a reaction mixture containing 100 g of sodium pyruvate, 50 g of pyrocatechol, 100 g of ammonium acetate, 10 g of sodium TABLE …”
Section: Mechanism Of By-product Formationmentioning
confidence: 99%
“…Its formation, therefore, seems to be due to the degradation of L-dopa or DL-serine to pyruvate by tyrosine phenol lyase in the cells and to the additional nonenzymatic reaction of pyruvate to L-dopa, known as the Pictet-Spengler reaction. 13 ) To isolate and identify X-I and X-2, 5 liters of a reaction mixture containing 100 g of sodium pyruvate, 50 g of pyrocatechol, 100 g of ammonium acetate, 10 g of sodium TABLE …”
Section: Mechanism Of By-product Formationmentioning
confidence: 99%
“…[18][19][20] Recently, we have explored ways to include basic nitrogen components in such sequences, [21][22][23][24] so that not only polyoxygenated, but also nitrogen-bearing, polycycles can be targeted. In a new method, 22,23 we combined the singlet oxygenphotooxidation of simple furans with the introduction into the reaction sequence of both a basic nitrogen reactant and a Pictet-Spengler cyclisation; [25][26][27] thus, affording in one operation various aromatic nitrogen containing-polycycles that are present in many natural products and other bioactive targets. This method, however, required the use of methanol and chlorinated solvents, neither of which can be part of a complete sustainable paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…1), [1] and has been found useful for the synthesis of tetrahydo-b-carbolines and tetrahydroisoquinolines and recently been proposed to be a common biosynthetic reaction for the construction of a range of alkaloids. [2] The reaction has been used to great avail in classic syntheses such as haemultine, [3] manzamine alkaloids, [4] yohimbinoid alkaloids, [5] and ecteinascidin 743.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Although the Pictet-Spengler reaction has been widely studied in indole and benzene chemistry, [7] less is known about the Pictet-Spengler cyclisation of other heterocycles such as imidazoles, an important component of many marine natural products. [8] In 1948, Folkers et al reported the first example of a Pictet-Spengler reaction between histidine and vitamin B 6 to form a tetrahydroimidazopyridine (1) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%